2021
DOI: 10.3390/ijms222212476
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NLRP3 Inflammasome in Lupus Nephritis

Abstract: Lupus nephritis (LN) is the most frequent and severe of systemic lupus erythematosus (SLE) clinical manifestations and contributes to the increase of morbidity and mortality of patients due to chronic kidney disease. The NLRP3 (NLR pyrin domain containing 3) is a member of the NLR (NOD-like receptors), and its activation results in the production of pro-inflammatory cytokines, which can contribute to the pathogenesis of LN. In this review manuscript, we approach the relation between the NLRP3 inflammasome, SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 89 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…After NLRP3 is activated, downstream molecules are recruited and assembled to form the NLRP3 inflammasome. Studies have shown that the NLRP3 inflammasome is overactivated in lupus nephritis, which promotes the exacerbation of inflammation and the progression of LN [ 29 , 31 ]. Based on previous findings, our results suggested that CD36 promotes podocyte injury by activating the NLRP3 inflammasome in lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…After NLRP3 is activated, downstream molecules are recruited and assembled to form the NLRP3 inflammasome. Studies have shown that the NLRP3 inflammasome is overactivated in lupus nephritis, which promotes the exacerbation of inflammation and the progression of LN [ 29 , 31 ]. Based on previous findings, our results suggested that CD36 promotes podocyte injury by activating the NLRP3 inflammasome in lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of autoimmunity is multifactorial, but interplay between various immune cells is critical [ 2 ]. Aberrant IFN signaling, activation of the NLRP3 inflammasome, as well as B cells and Th17 cells, and even hyperactivation of cytototoxic CD8 + T cells is noted [ 162 , 163 , 164 , 165 ]. Also, T and natural killer cells from SLE patients show higher intracellular ROS levels of than B cells from healthy controls; at the same time, Keap1 and Nrf2 levels are elevated as an antioxidant defense mechanism [ 166 ].…”
Section: Role Of Nrf2 Agonism In Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…The second signal is induced by PAMPs and DAMPs, which convert pro-caspase-1 to caspase by inducing the oligomerization of NLRP3. The resulting activated caspase-1 induces cell lysis or pyroptosis [39]. In particular, NLRP3 is involved in the pathogenesis or progression of kidney disease.…”
Section: Nod-like Receptors (Nlrs) As Pattern-recognition Receptors (...mentioning
confidence: 99%
“…In particular, NLRP3 is involved in the pathogenesis or progression of kidney disease. Ischemic reperfusion kidney injury induces cell damage or death by secreting DAMPs, which are also involved in rhabdomyolysis-associated acute kidney injury, as well as in lupus nephritis and systemic lupus erythematosus [39]. In addition, hypomethylation of NOD-1 and NOD-2, resulting in their aberrant expression, has been associated with chronic inflammatory diseases such as inflammatory bowel disease and rheumatoid arthritis.…”
Section: Nod-like Receptors (Nlrs) As Pattern-recognition Receptors (...mentioning
confidence: 99%